PERAN WAKAF PRODUKTIF DALAM PENGEMBANGAN PENDIDIKAN - Kasdi, Abdurrahman (Pascasarjana IAIN Kudus, 2015)
Productive communal ownership (waqf) represent especial choice when people is in the acute poorness. The existence communal ownership gets an especial priority addressed at more yielding effort. Productive communal ownership represent media to create justice of economics, lessening poorness, developing social security system, providing facility service of health, and developing the educational institution. This phenomenon make a productive communal ownership, and its relation with developing of education is very urgen to be done. This paper is the result of research that used a qualitative method with fenomenological approach, and analized by descriptive-explanative method. Through this method, the researcher tries to comprehend the model of enableness of productive communal ownership in al-Azhar asy-Syarif, Cairo in developing of education. As for model to study the enableness of productive communal ownership in al-Azhar asy-Syarif are: the model of enableness of productive communal ownership in managing of al-Azhar building, Hospital, student hostel, Islamic Research Institute, main library, the model of observation and the accuntability productive communal ownership, and the model of enableness of productive communal ownership for education.Wakaf produktif merupakan pilihan utama ketika umat sedang dalamketerpurukan kemiskinan akut. Dengan wakaf produktif, berarti wakaf yang ada memperoleh prioritas utama ditujukan pada upaya yang lebih menghasilkan. wakaf produktif merupakan media untuk menciptakan keadilan ekonomi, mengurangi kemiskinan, mengembangkan sistem jaminan sosial, menyediakan fasilitas pelayanan kesehatan, dan mengembangkan pendidikan. fenomena inilah yang menjadikan pembahasan wakaf produktif, terutama jika dikaitkan dengan pengembangan pendidikan sangat urgen untuk dilakukan. Makalah ini adalah hasil penelitian yang menggunakan metode penelitian kualitatif dengan pendekatan fenomenologis. Sedangkan metode kajian yang dipakai adalah metode kajian deskriptif-eksplanatif-analitis. Dengan pendekatan ini peneliti berusaha memahami model pemberdayaan wakaf produktif di al-azhar asy-Syarif, Cairo dalam pengembangan pendidikan. adapun model yang akan dikaji dari pemberdayaan wakaf produktif di al-azhar asy-Syarif ini adalah: model pemberdayaan wakaf produktif dalam pengelolaan gedung al-azhar, model pemberdayaan Rumah Sakit, model pemberdayaan asrama mahasiswa, model pemberdayaan lembaga Riset Islam, model manajemen al-azhar, model pemberdayaan wakaf Salah kamil, model pemberdayaan perpustakaan induk, model pengawasan dan akuntabilitas wakaf produktif, dan model pemberdayaan wakaf produktif untuk pendidikan.